AI-Assisted Design and Biochemical Optimization of Protein Structures for Enhanced Drug Delivery in Chemotherapy - Kaliaperumal, Kumaravel; S, Govindarajan; Ravi, Kamalam; Pranandi, Ian; Kumar, P Vinod; Gobinath, V M (Journal of Neonatal Surgery, 2025)
Chemotherapy remains the primary treatment for most malignancies; nevertheless, it is troubled by a handful of hindrances like non-specificity of the drug targeting agents, side effects, or actual drug resistance. Thus, protein engineering could be the answer to these problems by designing proteins capable of specific targeting of cancer cells, reducing unwanted drug toxicity, or carrying out controlled drug release. AI, in this regard, encompasses protein structure optimization for accelerated drug delivery and enhancement of the therapeutic efficacy. The present paper looks at AI utilization in protein engineering for drug delivery systems and its influence on chemotherapy, together with the possibility of using these innovations to combat existing challenges and enhance patient outcome.